The role of corruption in natural resource-financial development Nexus: evidence from MENA region - Chebab, Daouia; Mazlan, Nur Syazwani; Rabbani, Mustafa Raza; Chin, Lee; Ogiri, Ibrahim Aishatu (Faculty of Business and Economics, University of Malaya, 2022)
This paper contributes to the literature on resource curse by investigating the impact of natural resource abundance on financial development while accounting for the interactive effect of natural resources and corruption in 11 resource-rich MENA countries over the period of 1987 to 2015. Using pooled mean group (PMG) estimation technique, our results show that abundance of natural resource weakens the pace of financial development in countries with high level of corruption. Thus, resource rich countries in the MENA region will boost the level of financial development through minimising the degree of corruption in their financial sectors. Therefore, policymakers should control the corruption, which plays a significant role to mitigate the adverse effect of natural resources on financial development. This is through building strong institutions, which help to check corruption, enhancing rule of law and protecting investors. Our results are consistent and robust to alternative measures of natural resource abundance and financial development.